2019
DOI: 10.1186/s12867-019-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of reference genes for real-time quantitative RT-PCR analysis in jute

Abstract: Background With the availability of genome sequences, gene expression analysis of jute has drawn considerable attention for understanding the regulatory mechanisms of fiber development and improving fiber quality. Gene expression profiles of a target gene can provide valuable clues towards the understanding of its biological function. Reverse transcription quantitative real-time PCR (qRT-PCR) is the best method for targeted gene expression analysis due to its sensitivity and reproducibility. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…However, with our increasing understanding of the agricultural ecological value of non-model plants, it has become important to study their molecular genetic mechanisms and to determine their appropriate reference genes under different experimental conditions. To date, some non-model plants have been selected for research on internal reference genes, including Reaumuria 16 , Caragana intermedia 17 , Setaria viridis 18 , Miscanthus lutarioriparia 19 , Haloxylon ammodendron 20 , Hylocereus undulatus Britt 21 , and Corchorus capsularis L 22 .…”
mentioning
confidence: 99%
“…However, with our increasing understanding of the agricultural ecological value of non-model plants, it has become important to study their molecular genetic mechanisms and to determine their appropriate reference genes under different experimental conditions. To date, some non-model plants have been selected for research on internal reference genes, including Reaumuria 16 , Caragana intermedia 17 , Setaria viridis 18 , Miscanthus lutarioriparia 19 , Haloxylon ammodendron 20 , Hylocereus undulatus Britt 21 , and Corchorus capsularis L 22 .…”
mentioning
confidence: 99%
“…Many typical reference genes such as, UBQ, Actin, RPII, and CYP2, were isolated homologous sequences in plants [9,16,21]. In litchi, Zhong et al [50] reported the first litchi reference gene selection study.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in www.nature.com/scientificreports www.nature.com/scientificreports/ the ranking order has been observed in many studies and can be attributed to the different statistical approaches implemented in the algorithms 23,24 . To address this issue, a comprehensive ranking of reference genes was created based on the ranking value attributed by the algorithms geNorm, NormFinder and BestKeeper as performed previously [25][26][27][28] . Figure 3.…”
Section: Coefficient Correlation (R) Gene M Value Genementioning
confidence: 99%